Characteristics of disinfectants activity against multidrug-resistant clinical isolates: Disinfectants activity against multidrug resistant clinical isolates - Kovalchuk, Valentin; Vovk, Iryna; Kondratyuk, Vyacheslav; Nazarchuk, Oleksandr; Palii, Dmytro; Fomina, Nadiia (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: health-care associated infections (HCAI) significantly impair the quality and efficiency of medical care. Medical equipment`s parts are contaminated with opportunistic hospital strains leading to their spreading. Therefore, effective disinfection of medical equipment is one of the ways to solve a problem of HCAI. Methods: the research includes results of antimicrobial activity of biocides of different chemical structure (aqueous solutions of quaternary ammonium compounds, biguanides, oxidizers), which are used in medical practice as disinfectants for hospital environment, devices and equipment. Multidrug resistant clinical isolates with genetic markers of resistance were employed for comparative evaluation of ready-in-use germicides. Next microorganisms were used as test ones: clinical strains of methicillin-resistant S. aureus carrying mec A genes, carbapenemase-producing K. pneumoniae carrying blaOXA-48 gene, A. baumannii with blaOXA-72 gene, metallobetalactamase-producing P. aeruginosa carrying NDM-1 gene, strains of enterobacteria and non-fermenting gram-negative bacteria with a wide range of genes responsible for the production of aminotransferases that destroy aminoglycoside molecules. A quantitative suspension test was used to assess the activity of the tested biocides on some species of resistant microorganisms. Experimental study also includes antimicrobial efficacy testing of the disinfectant solutions, which was carried out on artificially contaminated with multidrug resistant clinical isolates fragments of polymer tubes of the respiratory circuit. Results: gram-negative bacteria showed a variable level of resistance to the studied germicides action, depending on the type of disinfectant solution and test microorganisms. Conclusions: the obtained results demonstrated that antibiotic-resistant strains of Gram-positive non-spore-forming bacteria were high susceptible to studied disinfectant solutions.